ПОРІВНЯЛЬНИЙ АНАЛІЗ ХАРАКТЕРИСТИК МОБІЛЬНИХ ЗАСОБІВ МЕТРОЛОГІЧНОГО ЗАБЕЗПЕЧЕННЯ - Тесик, Ю.Ф.; Карасінський, О.Л.; Мороз, Р.М.; Пронзелева, С.Ю.; Зайков, М.В. (Інститут електродинаміки Національної академії наук України, 2023)
A comparative analysis of the characteristics of portable calibrators with different principles of construction of channels for reproducing mode parameters of the electric network was carried out. The advantages and disadvantages of channels using current and voltage power output transformers are shown. It is proposed to combine the functions of impulse conversion and galvanic isolation in the channel of reproducing the mode parameters of the electric network. The advantages of transformerless channels for reproducing the mode parameters of the electric network are shown. The principle of operation of the devices is described, the structural diagrams and formulas reflecting the processes in the relevant circuits are given. The photo and characteristics of the calibrators of mode parameters of the electric network based on transformer and transformerless reproduction channels are given. Ref. 8, fig. 4, tables 2.